1993
DOI: 10.1007/bf01956748
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyl transferase I deficiency presenting as a Reye-like syndrome without hypoglycaemia

Abstract: An apparently healthy girl aged 2 years 9 months developed a coma with hepatomegaly within 24 h after an influenza-like infection. Plasma glucose and urinary organic acid profile were normal but plasma and urinary carnitine concentrations were increased. Despite symptomatic therapy, she died 11 days later. Oxidation of [1-14C] palmitic acid in the patient's fibroblasts was severely decreased (13% of controls). Further investigations revealed a deficiency of carnitine palmitoyl transferase I (CPT I) in the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…TBP-2 is also reported to be a causative gene for familial combined hyperlipidemia (FCHL) in mice. Individuals with genetic deficiencies in fatty acid transport and mitochondrial oxidation show a similar pathology to Reye syndrome, which is defined as a Reye-like syndrome, such as CPT-I deficiency [85] . Defects in different enzymes involved in fatty acid utilization give rise to different disorders.…”
Section: The Decreased Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…TBP-2 is also reported to be a causative gene for familial combined hyperlipidemia (FCHL) in mice. Individuals with genetic deficiencies in fatty acid transport and mitochondrial oxidation show a similar pathology to Reye syndrome, which is defined as a Reye-like syndrome, such as CPT-I deficiency [85] . Defects in different enzymes involved in fatty acid utilization give rise to different disorders.…”
Section: The Decreased Oxidationmentioning
confidence: 99%
“…There are reports linking Thioredoxin Binding Protein-2, a protein that interacts with thiredoxin which is an important redox regulator protein and Rye's syndrome. Individuals with genetic deficiencies in fatty acid transport and mitochondrial oxidation show a similar pathology to Reye syndrome, which is defined as a Reye-like syndrome, such as CPT deficiency [84,85] .…”
Section: The Fatty Liver Associated With Infectious and Immunologicalmentioning
confidence: 99%
“…Nineteen unrelated patients with CPT IA deficiency (Bergman et al 1994;Bonnefont et al 1989;Bougneres et al 1981;Brown et al 2001;Demaugre et al 1988;Falik-Borenstein et al 1992;Gray et al 1991;Haworth et al 1992;Innes et al 1997Innes et al , 2000IJlst et al 1998;Schaefer et al 1997;Stanley et al 1992;Tein et al 1989;Vianey-Saban et al 1993) and nine mutations in the CPT IA cDNA (Brown et al 2001;IJlst et al 1998;PripBuus et al 2001) have been reported to date. Detection of the molecular and biological findings of affected patients has an important impact on the elucidation of the structurefunction relationships concerning CPT IA.…”
Section: Introductionmentioning
confidence: 99%
“…The ®rst is localized in the mitochondrial matrix and reacts preferentially with short-chain substrates. The second is a membrane-bound trifunctional protein carrying not only long-chain 3-hydroxyacyl-CoA dehydrogenase activity but also long-chain enoyl-CoA hydratase and long-chain 3-ketoacyl-CoA thiolase activity [26]. More than 30 cases have been reported of patients suering from long-chain-hydroxyacyl-CoA dehydrogenase (LCHAD) de®ciency [1±3, 5, 9, 12, 14±17, 18, 20, 24, 24±31], but in the majority of these patients the trifunctional protein is present although its activity has been completely lost, with near-normal activity of the two other components.…”
Section: Introductionmentioning
confidence: 99%